Effect of combined thermal and water stress on germination of wheat seeds - Viviane de Souza Sartori, Altamara; Gaspar de Oliveira, Carolina Maria; Zucareli, Claudemir; Rodrigues Pereira, Alessandra; Sorane Good Kitzberger, Cintia; David dos Santos, Elizeu; Oliveira de Araújo, Flávia (Revista Ciência Agronômica, 2022)
Combined abiotic stresses have different effects and responses than exposure to a single source of stress. The objective of this study was to evaluate the effect of the combined stress of supra-optimal temperatures and water deficit on the germination of wheat seeds with different levels of vigor. Wheat seeds from four different lots of the IPR Catuara cultivar were germinated at water potentials of 0.000, –0.075, –0.223, and –0.444 MPa, associated with temperatures of 20 °C, 24 °C, 28 °C, and 32 °C, totaling 16 stress combinations. The experimental design was completely randomized in a factorial scheme with four replications (four seed lots × 16 stress combinations), and means were compared using Scott-Knott 5%. We evaluated the germination of normal seedlings at 4 and 8 d, the activity of catalase and ascorbate peroxidase (APX), and the protein content of the aerial and root parts of wheat seedlings. Principal components analysis and hierarchical clustering were applied to the original matrix formed by the 16 combinations for the average of the four lots. Wheat seeds with higher vigor were more tolerant to combined water and thermal stress. Temperatures up to 28 °C and reduction of water potentials down to –0.223 MPa did not prejudice the germination process of wheat seeds. Regardless of temperature, a water potential of –0.444 MPa decreased the percentage and rate of germination. APX activity increased under water stress and supra-optimal temperatures, acting as a defense mechanism against oxidative stress.